Difficulties in positioning as veg*an: Two distinctions to examine positioning - Gfeller, Fabienne (My University, 2023)
Positioning and position are notions that are quite often used currently in psychology, mostly with reference to Dialogical Self Theory and Positioning Theory. In this article, drawing on these two approaches as well as on socio-cultural psychology, I elaborate an integrative understanding of positioning. It includes a distinction between the socio-material, socio-discursive and moral dimensions of positioning, as well as a distinction between microgenetic, ontogenetic and sociogenetic scales of positioning. I illustrate the hermeneutical power of this theoretical proposition through the presentation of a study of positioning regarding the consumption of products of animal origin. I present an analysis of data collected in 2016 in a Swiss canton with qualitative semi-structured interviews with 10 participants. I focus on difficulties in positioning and show how the classical approach in terms of I-positions, and analyses based on the two distinctions presented above, allow differentiated insights on dynamics underlying the difficulties to position as a vegetarian or vegan.
Keywords: positioning; veg*ism; ontogenetic/microgenetic/ sociogenetic; moral positioning; socio-discursive positioning